Westward the women [videorecording (DVD)] - Capra, Frank, 1897-1991; Eyman, Scott, 1951-; Taylor, Robert, 1911-1969; Darcel, Denise, 1924-2011; Emerson, Hope, 1897-1960 (Archive collection., 2012)
They are rugged pioneers, Indian fighters and brave trailblazers who tame the wild west. These are the women of the great frontier. Buck Wyatt is a tough, experienced scout who leads a wagon train comprised of two ex-show girls, a hearty widow and fifteen men who act as guides. When one of the men disobeys Buck's orders not to fratenize with the ladies, Buck shoots him, causing the others to desert. The determined women insist on going on, learning to ride, shoot and drive mules.